AMBASSADOR PLENIPOTENT FROM KOKAND - Nuridinov Turdali Qambarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article highlights the young years of a prominent statesman, Ambassador of the USSR N. Tyurakulov associated with the city of Kokand.